Leveraging Candidate Feedback to Support Early Field Experiences for PK-3 Pre-Clinical Teacher Candidates - Katie Moses; Susan Harte; M. Dawn Gatlin (Texas Educator Preparation, 2026)
This study investigated the perceived comfort levels of PK-3 pre-clinical teacher candidates before and after their first semester of field experience to identify potential gaps in curriculum, instruction, or program design. The Field One Experience (FOE) involved weekly, full-day placements over eight weeks in a public-school classroom with the same mentor teacher. Using a paired-samples t-test, the study found statistically significant gains in candidates’ confidence related to observing classroom instruction (Q1, p = .012), engaging in hands-on teaching activities (Q4, p = .002), and developing relationships with students (Q9, p = .030). Additional areas showed positive but non-significant trends. However, comfort levels remained low in domains such as educational technology, assessment practices, and school-community engagement, highlighting areas for targeted instructional and experiential support. These results underscore the value of early field experiences while pointing to specific opportunities for program enhancement.